THE RELATIONSHIP BETWEEN SELF-ESTEEM AND INTERPERSONAL RELATIONSHIP WITH BODY IMAGETO STUDENTS AT THE ALI BIN ABI TALIB TANJUNG MORAWA MIDDLE SCHOOL - Siti Aisyah; Dewi Ardianita; Patisina (RADJA PUBLIKA, 2023)
The purpose of this study is to determine the correlation between self- esteem and interpersonal relationship with body image. Using quantitative methods with a survey approach. A sample of 88 people from 118 populations with purposive sampling technique. Based on the results of the analysis using the linear regression analysis method, it is known that there is a positive and significant correlation between self- esteem and body image seen from the coefficient value (R2 ) = 0.244 with p = <0.050.